Cryogenic treatment and taguchi optimization of Haynes alloy. (2022) - Rajkumar, M.; Senthil Kannan, N.; Bruhathi, M.; Malteshkumar, D.; Girisha, L.; Felix Sahayaraj, A.; Subbiah, Ram
Highlights: Haynes 214 alloy was kept under −190 °C in the cryo processor equipment. The properties such as hardness and wear rate were computed. The cooling rate, flow rate of nitrogen and holding time were monitored. The desired response factors were attained and optimized by Taguchi method. The role of factor and its involvement has been verified through variance test. Abstract: The substance properties were enhanced gradually through cryogenic treatment. The current experimental investigation has reported the enhanced substance properties of Haynes alloy. The substance properties of Haynes 214 alloy has not been increased by conventional technique. It has better properties and it consists of nickel, chromium, aluminium and iron based alloy. In this process, the alloys were treated to −190 °C. The cryogenic treatments were performed with the help of cryo processor. The alloy properties of hardness and wear rate were estimated with respect to the different control factors. Taguchi approach was utilized to determine the desired response factors. The effect of factors and its involvement have been investigational through variance test.